Psychological PSYCHOLOGICAL CONFLICTS OF REBECCA’S CHARACTER IN “THIS FAR FROM PARADISE” NOVEL BY PHILIP SHELBY - Lodo, Rozita Yusniaty (LP3MKIL, 2022)
“This Far from Paradise” is all about a feisty young woman who fights to regain control of her dead father's Caribbean empire. Max McHenry is a grizzled old prospector straight out of Treasure of the Sierra Madre when he makes a fabulous gold strike and shrewdly builds a financial empire on it, becoming practically king of a group of Caribbean islands called the Angelines. In the novel entitled “This Far from Paradise” written by Philip Shelby, the writer wants to find the way how the characters show their role to give the reader the meaning of the novel, how the story goes. The research methodology is the qualitative method. There are some steps done by the writer in doing the research. Firstly, the writer reads the novel by Philip Shelby which entitled “This Far from Paradise”, and tries to understand its content. Secondly, the writer reads some other references that are related to the study. Furthermore, the writer applies the psychoanalysis theory of personality by Sigmund Freud concerning trauma, anxiety, and the defense mechanism.